E-025 Initial Multicentre Experience Using the Penumbra 5Max, 4MAX and 3MAX Reperfusion Catheters in Acute Stroke Therapy. (14th July 2013) - Farkas, J; Arcot, K; Kumar, R; Delbrune, J; Papamitsakis, N; Margulis, Y; Walzman, D; Dash, S; Levin, K; Azhar, S
Abstract : Purpose: The Penumbra MAX System (5MAX, 4MAX, and 3MAX) refers to a new generation of reperfusion catheters with a larger, tapered lumen and new material composition in the distal end designed to enhance aspiration efficiency with improve trackability. Results from a retrospective multicentre study with the Penumbra System 5 MAX, 4MAX and 3MAX reperfusion catheters in acute stroke patients with large vessel occlusion are reported. Methods: A retrospective case-review of 22 consecutive acute ischaemic stroke cases from July 2012 through March 2013 treated by the Penumbra System (5 MAX, 4MAX and 3MAX) was performed. The case experience from three institutions was collected in the initial months after the device was released. Results are reported from cases which involved occlusions in the ICA (n=6), proximal MCA M1 (n=10), distal MCA M2 (n=3) and vertebrobasilar arteries (n=3). Results: Prior to intervention, all patients presented with TICI 0 or 1. Successful revascularisation was primarily achieved in 86.3% (Tici 2b & Tici 3 ) using the Penumbra System with 5 MAX, 4MAX and 3MAX reperfusion catheters. Mean age was 71.45 ± 14.4 years; median baseline NIHSS score was 20.5 ± 3.96. In 1 patient, embolisation of new territory was found and treated by IA rtPA. One case of intracerebral haemorrhage (ICH) was noted with haemorrhage in a previously unaffected region, possibly secondary to IV rtPA treatment. Conclusion: Early clinical experience suggests that the 5 MAX, 4MAX and 3MAX appear to have improved aspiration efficiency and tracking. Follow-up data and additional cases are critical in confirming these initial results. Disclosures: J. Farkas: None. K. Arcot: None. R. Kumar: None. J. Delbrune: None. N. Papamitsakis: None. Y. Margulis: None. D. Walzman: None. S. Dash: None. K. Levin: None. S. Azhar: None.